The embodied, relational self: extending or rejecting the mind? - Gough, J (Routledge, 2022)
In putting forward the modern concept of mind, Descartes identified the mind with the self. Recently, communitarian and feminist scholars have argued in favor of a conception of the self according to which it includes relations to the social world and parts of the body. If they are correct, it initially seems damning for the view that the self is the mind. I examine whether this is so, by considering whether the identification of self and mind can be saved by recent views of the mind according to which it is partly constituted by aspects of the body other than the brain and by the world beyond the skin. I argue that it cannot, before considering what this means for the mind and its relationship to selves and persons.